(3QSGdI aj GdQShe GdeQSheI Ydi GdGSWQdGH GdTeGdjs - (3eLghds
(3ChdgG (B:s
(3GdMeO ddg agPg QSGdI eNJUQI CPcQ ajgG GdQShe GdeQSheI Ydi GdBdGJ GdeSeGI HGdGSWQdGH GdTeGdj PGJ GdUaGFM hHYV CYeGdgG hgj eTJedI Ydi ebOeI hNeSI YTQ aUdG hNGJeI s
(3BNQgG (B:s
(3hJfXQ GdNW GdNGQL ef GQJaGY GdhbJ ef NWhW GdLjhH Gdi Gf jJbGWYG aJNQL GdJbGWY Gdi eY GdeOGO GdebGWY dgeG Ke JfRd ef GdLjH GdNGQL ef Pdc GdehVY Jes
(3eUOQ GbJfGA GdCUd (B:s
(3Ydj CejQjs
(3ehGUaGJ GdhYGA (B:s
(3Qbej edhfs
(3ehGUaGJ GdfSNI (B: s
(3MGdI GdfSNI (B:s
Keywords: (3Gdadc hGdJfLje hGdejbGJs